PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 008 BUKIT KAPUR - M. Asroi '; Hendri Marhadi Hendri Marhadi; Gustimal Witri Gustimal witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract.This research represent the Research of Class Action (CAR) conducted to increase result of learning student of class of IV SDN 008 Bukit Kapur by applying model the study of co-operative of type of Group Investigation ( GI). This Research  is   conducted at April  2014 executed by 2 is cycle. this Subjek Research  is  student of class of IV SDN 008 Bukit Kapur amounting to 34 one who is made by a data source. Instrument  of  data collecting of at  this research is  sheet of activity perception learn and student and also result of learning. Mean of  result of learning previous student that is 60,7 from 34 complete student people only 10 completely is klasikal 29,4% while student which is not complete 24 people completely is klasikal 71,6%. At this research is presented by a activity percentage learn and student and also result of daily restating of cycle of I and cycle II. Activity Percentage learn at cycle of I and II is 57,9% mounting to become 79,2%. percentage of student Activity of at cycle of I and II is 45,9% mounting to become 75% Mean of result of learning student of  at cycle I  is 73,6 from 34 student, complete 25 people with the percentage 73,5% and which is not complete 9 people with the percentage 27,5%. Mean of result of learning student of cycle II is 77,1 from 34 one who complete 31 people with the percentage 91,7%. Inferential thereby that applying model the study of co-operative of type of Group Investigation (GI) if can improve the result learn the student of class of IV SDN 008 Bukit Kapur. Keywords : Model The Study of Co-Operative of Type of Group Investigation, Result of Learning IPS.